PERAN NOTARIS DALAM PERLINDUNGAN HUKUM TERHADAP PEMEGANG SAHAM MINORITAS - , Reny Permatasari Gumay; , Prof. M. Hawin, S.H., LL.M., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ABSTRACT The research aims at identifying and analyzing legal protection for minority shareholders based on the Law No. 40 Year 2007, legal measures that can be taken by minority shareholders if their rights are violated, as well as the roles of notary in providing legal protection for minority shareholders subsisted in the LLC Deeds of Association. The research belongs to normative legal research, which emphasizes on library study to obtain secondary data library research to obtain secondary data as primary data. To support and complement the data, then conducted field research as a complement. All data is then analyzed using qualitative descriptive methods. The research concludes that: (1) in providing protection toward minority shareholders, a specific protection that agrees with stipulations written on Article 53 clause 2 is necessary. It must be accompanied with good corporate governance principle so that conflicts of interests can be controlled so as to avoid disadvantages for the minority shareholders